Analisis Rasio Keuangan, Firm Size, Free Cash Flow Economic Value Added Dan Market Value Added Terhadap Return Saham - Tudje, Muchlis (Universitas Sam Ratulangi, 2016)
The purpose of this research is to examine whether the current ratio, ROE, DER, PBV, Firm size, FCF, EVA and MVA has effect on return share in partially and simoustinously, analysistechnic used in this research is quantitative analysis, the method is regression. The population in this research is consumer good firm in IDX, and the sampling method is purposive sampling. The findings in this research is TATO, firm size and FCF has effect partially on return share while current ratio, ROE, DER, PBV, EVA and MVA has no effect on return share and simoustinously current ratio, ROE, DER, TATO, PBV, firm size, FCF, EVA, MVA has effect on return share.Keywords: Current ratio, ROE, DER, TATO, PBV, Firm Size, FCF, EVA, MVA, return share.